Experimental Apparatus for Vibration Analysis in Robotics - Lima, Miguel F. M. (2019)
Robotic systems use different types of sensors both in control and in environment perception. Those sensors can be digital encoders, tachometers, accelerometers, force sensors,current sensors and many others. In this paper an experimental setup is presented to study vibrations and impacts. The system acquires data from the sensors, in real time, and, in a second phase, processes it through an analysis package. Several examples with experimental results are carried out showing the functionalities of the developed apparatus.